Realism and Relevance in Consumer's Surplus - Mishan, E. J. (Review of Economic Studies, 1947)
Journal Article Realism and Relevance in Consumer's Surplus Get access E. J. Mishan E. J. Mishan London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 1, 1947, Pages 27–33, https://doi.org/10.2307/2295925 Published: 01 April 1947